Prevalence of Systemic Hypertension among the rural residents of Kerala - Prasanth TS , Vijayakumar K (Calicut Medical Journal 2008;6(3):e4, 2008)
Systemic Hypertension is the "silent killer" of our times throughout the world. It isassociated with target organ damage, such as chronic kidney disease, coronary arterydisease, stroke and sudden death. We did the study to analyse if there is any relationbetween age and gender in the prevalence of systemic hypertension in rural kerala.Data was procured from the PROLIFE database on non-communicable diseases with subjects spanning over 3422 conducted in two wards of Chemmaruthy panchayatharea, Varkala, Kerala. Blood pressure was measured using OMRON electronic deviceusing house visits and analysed. It revealed that about 33.5 per cent of the total subjects were hypertensive with 65.6 per cent of those above 60 years affected. The prevalence increases with age in both genders and females are more vulnerable after menopause. So we should expect a catastrophic increase in the casualties due to the complications of hypertension in the near future in Kerala.